A sonochemical approach for the synthesis of thermally stable mesoporous microspheres of TiO2 for use as high performance anodes for Li-ion batteries. (29th June 2016) - Sunkara, Satyendar; Munichandraiah, N.; Varma, K. B. R.; Shivashankar, S. A.
Abstract : Microspheres of anatase TiO2 exhibiting excellent cycling stability as anode materials for Li-ion batteries have been prepared by sonochemical synthesis. Abstract : A facile, surfactant-free sonochemical synthesis route at a relatively low temperature was employed to prepare mesoporous microspheres of anatase titanium dioxide (TiO2 ), using the heteroleptic (mixed-ligand) complex, bis-isopropoxy-bis-tertiarybutylacetoacetatotitanium, [Ti(O i Pr)2 (tbaoac)2 ], as the precursor. The transformation of the as-prepared material into crystalline TiO2 was achieved by heating in air at 500 °C. Interestingly, the material retained its pure anatase phase even after heating at 800 °C. The as-prepared sample and the heated ones were characterized by powder X-ray diffraction (PXRD), X-ray photoelectron spectroscopy (XPS), and electron microscopy (SEM, TEM) which, together, revealed that the spheres are mesoporous and, significantly, hollow. As an anode material in a Li-ion battery, the titania microspheres exhibited a high reversible capacity of 212 mA h g −1 after 100 charge and discharge cycles and displayed excellent cycling stability.